Pernambuco Caatinga: relevance of soil chemical composition for biodiversity conservation. Issue 2 (7th February 2022) - Herrero Fernández, Zahily; dos Santos Júnior, José Araújo; dos Santos Amaral, Romilton; De França, Elvis Joacir; Menezes, Rômulo Simões Cezar; Brayner Cavalcanti Freire Bezerra, Mariana; Paiva Coutinho, Artur; Valcarcel Rojas, Lino Angel; Santos, Josineide Marques do Nascimento; Dias Bezerra, Jairo; Nóbrega de Araújo, Eduardo Eudes
ABSTRACT: Besides being one of the most threatened forests, the Brazilian Seasonally Dry Tropical Forest (Caatinga) is the least studied ecosystem in the Northeast Region. Soil composition has an important role in biodiversity conservation since the Caatinga suffers from degradation, salinisation and desertification, mainly caused by non-sustainable agriculture and urbanisation. To identify priority areas for Caatinga preservation, it is necessary to know the nutrient content of the soil and other chemical elements, with information from a consistent and reliable database. The present work aimed at the quantification of Al, Ca, Fe, K, Mg, Mn, Ni, Pb, Si, Sr, Ti and Zn. All chemical elements were determined by Energy Dispersive X-Ray Fluorescence – EDXRF. Multivariate statistical techniques applied to soil identified the correlation between the chemical elements determined in diverse Caatinga soil types. Multivariate analysis when combined with the accumulation index indicates soils where the use of conservation units could be recommended. Research on the behaviour of these elements in the soil, to find solutions or control methods, may lead to a reduction of the risk of environmental degradation.